Głos Solidarności . wydanie specjalne biuletynu "Solidarność Walcząca", no. 12, 1990 - Ciechanowicz-, Sarata, Aleksandra; Lipski, Paweł; Wiśniewski, Walerian; Drewnicz, Dariusz; Marszal, Krzysztof; Mirecki, Tadeusz ([s.n.], 1990)
Print run: 4000-15000 copies